Ketikdakstabilan Kadar Glukosa Darah Pada Pasien Diabetes Melitus Tipe II - Nur Syamsi Norma Lalla; Jena Rumatiga (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Diabetes mellitus is a metabolic disorder characterized by an increase in blood glucose levels (Hyperglycemia) due to damage to insulin secretion and insulin work; daily blood glucose levels vary, and blood sugar levels will increase after eating and return to normal within 2 hours. Purpose: To determine the instability of blood glucose levels in patients with type II diabetes mellitus. Method: Design qualitative research with a study approach, a method carried out to expose or describe the actual situation. Results: There was a gap between patient 1 and patient 2 in the study results. In patient 1, it was found that the patient had anemic conjunctiva, and patient 2 had no complaints of anemic conjunctiva. This happens because low hemoglobin levels can prove the presence of iron deficiency anemia. Serum protein levels provide an estimate of offal protein deposits. Conclusion: The problem of nursing instability of blood glucose levels in patients has not been resolved because the blood glucose levels of both cases have not stabilized/are normal.